The Transcription Factor OsWRKY45 Negatively Modulates the Resistance of Rice to the Brown Planthopper Nilaparvata lugens - Huangfu, Jiayi (Int J Mol Sci, 2016)
WRKY transcription factors play a central role not only in plant growth and development but also in plant stress responses. However, the role of WRKY transcription factors in herbivore-induced plant defenses and their underlying mechanisms, especially in rice, remains largely unclear. Here, we cloned a rice WRKY gene OsWRKY45, whose expression was induced by mechanical wounding, by infestation of the brown planthopper (BPH, Nilaparvata lugens) and by treatment with jasmonic acid (JA) or salicylic acid (SA). The antisense expression of OsWRKY45 (as-wrky) enhanced BPH-induced levels of H(2)O(2) and ethylene, reduced feeding and oviposition preference as well as the survival rate of BPH, and delayed the development of BPH nymphs. Consistently, lower population densities of BPH on as-wrky lines, compared to those on wild-type (WT) plants, were observed in field experiments. On the other hand, as-wrky lines in the field had lower susceptibility to sheath blight (caused by Rhizoctonia solani) but higher susceptibility to rice blast (caused by Magnaporthe oryzae) than did WT plants. These findings suggest that OsWRKY45 plays important but contrasting roles in regulating the resistance of rice to pathogens and herbivores, and attention should be paid if OsWRKY45 is used to develop disease or herbivore-resistant rice.